2004
DOI: 10.1002/ijc.20164
|View full text |Cite
|
Sign up to set email alerts
|

Association between war and cervical cancer among Vietnamese women

Abstract: Decades ago, cervical cancer was the leading form of cancer among women in both North Vietnam and South Vietnam. Currently, cervical cancer rates are considerably lower in the northern region of the country. We performed a case-control study to measure factors associated with the development of cervical cancer among Vietnamese women. Questionnaire-based interviews were conducted with 202 women in southern Vietnam and 97 women in northern Vietnam. Case subjects were women hospitalized with cervical cancer. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…This study is limited by the axiom that not all associations are causations. The association between the Vietnam War and cervical cancer5 may have no causative meaning. The association between de novo establishment of Papanicolaou screening services in southern Vietnam2, 9 and subsequent reductions in cervical cancer incidence may also have no causative meaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is limited by the axiom that not all associations are causations. The association between the Vietnam War and cervical cancer5 may have no causative meaning. The association between de novo establishment of Papanicolaou screening services in southern Vietnam2, 9 and subsequent reductions in cervical cancer incidence may also have no causative meaning.…”
Section: Discussionmentioning
confidence: 99%
“…American volunteers interested in cervical cancer prevention first visited Vietnam in January 1994,2 and were promptly presented with population‐based tumor registry data documenting cervical cancer incidence rates five times higher in southern Vietnam3 relative to northern Vietnam 4. A 1996 case‐control study sponsored by Stanford University documented that these regional variations in cervical cancer incidence rates were associated with prior troop movements during the Vietnam War 5…”
mentioning
confidence: 99%
“…Three studies assessed cervical cancer incidence ( Figure 2, bottom right panel). One moderate-to-high quality case-control study of the Vietnam War showed that women with a husband in the army had higher odds of cervical cancer compared to those without (adjusted odds ratio (AOR) 1.32, 95% CI: 1.00-1.75) [42]. One low-quality ecological study in Greece assessed over 35,000 smear tests from hospitals with different proximity to the Yugoslav border, but showed no difference in either cervical cancer or cervical intraepithelial neoplasia incidence between the sites following the NATO bombing of Yugoslavia in 1999 [43].…”
Section: Cervical Cancer Incidencementioning
confidence: 99%
“…Additionally, during the war with the USA, commercial sex outlets catering to US soldiers were common in the south . A study found that women whose husbands served in the military during the war and were stationed in south Vietnam had an increased risk of cervical cancer . More recently, urbanisation and higher disposable incomes have led to more sex outside marriage, particularly in southern Vietnam…”
Section: Introductionmentioning
confidence: 99%